AGASSIZ 1916 - Junior Photos - North Dakota Agricultural College (Fargo, N.D.); Fargo (N.D.); (North Dakota State University Library, University Archives;, 1916)
1916 Agassiz 1916 Katherine Ladd Fargo, N.D. Agricultural and Manual Training High Home Economics Edwin Booth Dramatic Club, Pythian, Y.W.C.A. Delta Phe Beta Treasurer, Winner of 1915 Declam. Less talkative than her twin sister. Is breaking in a new crush so she will not be alone when Miss York goes. Very fond of slumber parties. A former assistant in gym work. Her winning countenance never fails to influence the judges in forensic contests. “Actresses will happen in the best of regulated families.” Rizpah Ladd Fargo, North Dakota Agricultural and Manual Training High Home Economics Pythian, Edwin Booth Dramatic Club, Y.W.C.A., Delta Phi Beta. Which one of the twins? The laughing one. Plays gentleman friend to all the “Spinsters” on the Faculty. Has a delicate appetite, and as a result, others benefit. Bundles up to walk a block to school, as if she were going on a North Pole Expedition. Has a failing for plaid skirts. Exchanges Yearly Courtesies with Phil Schuyler. “A good laugh is sunshine in a house.” Robert Bruce McKee Fargo, N.D. Agricultural and Manual Training High Agriculture Letter Club, Philomathian, Basket Ball 1913-’15, Captain Elect for coming year, Alpha Gamma Rho. “Bruce” is beyond reproach. He has such winning ways when amongst the girls. Takes special pains in combining his hair and pressing his trousers. Is a regular visitor at Ford’s establishment on North Broadway. Bruce is one of our old timers in basket ball. “The girls are on his trail.” Viewbooks; 27 x 20 cm. Title taken from cover of book